Photochromic nucleosides and oligonucleotides - Bargstedt, Jörn; Reinschmidt, Martin; Tydecks, Leon; Kolmar, Theresa; Hendrich, Christoph; Jäschke, Andres (Angewandte Chemie. International edition, 2023)
Photochromism is a reversible phenomenon wherein a material undergoes a change in color upon exposure to light. In organic photochromes, this effect often results from light-induced isomerization reactions, leading to alterations in either the spatial orientation or electronic properties of the photochrome. The incorporation of photochromic moieties into biomolecules, such as proteins or nucleic acids, has become a prevalent approach to render these biomolecules responsive to light stimuli. Utilizing light as a trigger for the manipulation of biomolecular structure and function offers numerous advantages compared to other stimuli, such as chemical or electrical treatments, due to its non-invasive nature. Consequently, light proves particularly advantageous in cellular and tissue applications. In this review, we emphasize recent advancements in the field of photochromic nucleosides and oligonucleotides. We provide an overview of the design principles of different classes of photochromes, synthetic strategies, critical analytical challenges, as well as structure-property relationships. The applications of photochromic nucleic acid derivatives encompass diverse domains, ranging from the precise photoregulation of gene expression to the controlled modulation of the three-dimensional structures of oligonucleotides and the development of DNA-based fluorescence modulators. Moreover, we present a future perspective on potential modifications and applications.